2016
DOI: 10.1016/j.agee.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A new role for pond management in farmland bird conservation

Abstract: 1. Biodiversity declines in agricultural landscapes represent a major conservation challenge. In the UK, some agricultural landscapes contain high pond densities, but many farmland ponds have become terrestrialised since the 1960s, with input of organic material resulting in a decrease in the size and depth of ponds that eventually transform into wet woodland habitats. Pond management, including removal of overhanging scrub and sediment, has proven highly effective in enhancing freshwater biodiversity. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…The effects of changing habitat quality will vary according to the nature of the deterioration and some species may actually benefit, although generally not conservation-priority species. For example, ponds overtaken by scrub are poor for aquatic bird species, but provide habitat for various scrub- species, such as warblers ( Davies et al, 2016 ). Similarly, eutrophication could enhance food resources for birds that exploit emergent Chironomidae, although ephemeral flushes of invertebrate food abundance (e.g.…”
Section: Deterioration In Biological Communities Of Swbsmentioning
confidence: 99%
“…The effects of changing habitat quality will vary according to the nature of the deterioration and some species may actually benefit, although generally not conservation-priority species. For example, ponds overtaken by scrub are poor for aquatic bird species, but provide habitat for various scrub- species, such as warblers ( Davies et al, 2016 ). Similarly, eutrophication could enhance food resources for birds that exploit emergent Chironomidae, although ephemeral flushes of invertebrate food abundance (e.g.…”
Section: Deterioration In Biological Communities Of Swbsmentioning
confidence: 99%
“…Farmland ponds afford crucial oases within intensively managed agricultural landscapes, contributing to habitat heterogeneity (Benton et al 2003), and to aquatic and terrestrial biodiversity (Williams et al 2003, Davies et al 2016. Despite their ecological importance, over 50% of farmland ponds in the UK have been lost during the last century, with many filled in due to agricultural land consolidation (Hassall 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ponds have clearly been shown to have enormous value for amphibians (Beja & Alcazar, 2003;Knutson et al, 2004), invertebrates (Cayrou & CĂ©rĂ©ghino, 2005;Friday, 1987;Williams, 1997), and other groups of organisms (Davies et al, 2016;SebastiĂĄn-GonzĂĄlez et al, 2010). Soomets et al (2016) demonstrated that ponds constructed for amphibians also serve as habitat for many other Downing et al, 2008).…”
Section: Ponds Provide Important Habitatmentioning
confidence: 99%